Aktor non-negara : kajian implikasi kejahatan transnasional di Asia Tenggara - Aktor_non-negara:_kajian_implikasi_kejahatan_transnasional_di_Asia_Tenggara (Yayasan Pustaka Obor Indonesia, 2018)
id,2/why, c.1-2